(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess patients’ perceptions of the quality of outpatient medical services at the Outpatient Department of Thong Nhat Hospital. Subjects and methods: A cross-sectional descriptive study was conducted on 265 outpatients from February to March 2025. Data were collected using a structured questionnaire based on the SERVPERF model, consisting of 22 items evaluating five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Results: The majority of participants were female (58.1%) with a mean age of 48.8 ± 17.7 years; 86.4% had at least a high school education; 72.8% had visited the hospital more than three times. The mean scores for the five SERVPERF dimensions were: tangibles (4.53 scores), reliability (4.49 scores), responsiveness (4.52 scores), assurance (4.61 scores), and empathy (4.52 scores), with an overall average of 4.53 out of 5 scores. Conclusion: Patients rated the quality of outpatient services at the Outpatient Department of Thong Nhat Hospital as high across all SERVPERF dimensions, particularly in professional competence and staff dedication. These findings provide valuable insights for sustaining and improving service quality in similar healthcare settings.